Guillain-Barré Syndrome Associated with Primary Parvovirus B19 Infection in an HIV-1-Infected Patient - Caroline Bucher Praz; Cédric Dessimoz; Frank Bally; Sitthided Reymond; Nicolas Troillet (Case Reports in Medicine)
Parvovirus B19 (B19V) infection has rarely been reported as responsible for Guillain-Barré syndrome (GBS). We present the case of a 63-year-old man with AIDS who presented with rapidly progressing weakness of his inferior limbs and a newly appeared pancytopenia. CSF examination and electromyography were characteristic for GBS. Very high CSF and serum B19V DNA concentrations were present, in the absence of IgG or IgM against B19V. The neurologic and hematologic abnormalities improved after a 5-day course of i.v. immunoglobulins in parallel with a dramatic decrease in the B19V viral load.